Facile preparation of palygorskite/chitin nanofibers hybrids nanomaterial with remarkable adsorption capacity - Stanley Chinedu, Mamah; Pei Sean, Goh; Ahmad Fauzi, Ismail; Mohamed Afizal, Mohamed Amin; Nor Akalili, Ahmad; Nur Diyana, Suzaimi; Yusuf Olobode, Raji (Elsevier B.V., 2020)
A novel hybrid nanomaterials comprising of palygorskite (PAL) and chitin nanofibers (ChNFs) was successfully synthesized via simple, green and cost effective technology/method and for the first time used in adsorption process. Shrimp sourced chitin is a biopolymer endowed with amino and hydroxyl groups suited for adsorption of metals while PAL is hydrophilic, cheap and eco-friendly material. The hybridization of PAL and ChNFs was achieved under the collision and shear force of ball mill. Morphological analysis showed that ChNFs were attached on PAL leading to enhanced stability of the hybrid dispersion. PAL/ChNFs was used as an adsorbent for Pb(II) ion metal removal. The hybrid adsorbent showed a remarkable adsorption capacity (qe) of 53.7 mg g−1 and removal efficiency of 92.9%. This water dispersible PAL/ChNFs holds great potential in different water treatment related applications that require materials with high hydrophilicity, anti-fouling, biocompatibility, adsorption as well as mechanical properties.